Transportation and temp agency work: Risks and opportunities for migrant workers - Hanley, Jill; Salamanca Cardona, Manuel; Henaway, Mostafa; Larios, Lindsay; Dwaikat Shaer, Nuha; Ben Soltane, Sonia; Eid, Paul (Cahiers de géographie du Québec, 2018)
Access to transportation has long been recognized as key to people’s employment outcomes. Being able to get to work affordably, safely and on time makes all the difference in terms of job security and satisfaction. Recently, the rise of temporary placement agencies, especially as a gateway into the labour market for many newcomers to Canada, raises new questions. In this article, we present the findings of a 3-year longitudinal study that followed 42 (im)migrant temp agency workers in 5 sectors to explore the trajectory of their experiences. We analyze the role of transportation within their employment and make the argument that access to transportation—and especially the lack of it—is an important factor in temp agencies’ control and exploitation of workers. At the same time, those seeking to help workers can look into their work commute as a place of intervention.